The Primary Schools’ Academic Affairs Administration in Salavan District, Salavan Province - SYLISONGKHAM, Somboun; NORDALA, Phouvong; KHAMMELEESAYSUE, Her; DUANGCHAN, Boy; XAYDUANGTA, Sulinthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This study focused on the academic administration of Primary Schools in Salavan District, Salavan Province. The key objectives were: 1). to investigate the academic administration, 2) to compare the opinions of administrators and teachers concerning the academic administration classified by sex, position, qualification and teaching experience and 3) to find out the strategies for further development of academic administration. The target group consisted of 94 administrators and 123 teachers. The research tool was the 5 rating scales questionnaire. The computer software program was used for data analysis to find out the frequency, percentage, mean, standard deviation; and the hypothesis was analyzed by t-test and F-test for the differentiation of each variable. The research results were as follows: the academic administration of Primary Schools in Salavan District was generally ranked at good level. When considering individual aspect, all of them were at good level and the highest one was the assessment and evaluation administration; followed by the administration of learning and teaching, curriculum, internal monitoring and learning-teaching materials respectively. The results of the administrators’ and teachers’ opinions on the academic administration of Primary Schools in Salavan District, Salavan Province, showed that there is no significant difference in terms of the administration of the curriculum, teaching and learning, materials, assessment and evaluation, and internal monitoring, and the guidelines for the administrative work of the primary school in Saravane district, Saravane province are as follows: the curriculum must be updated to suit the age of the students, the school must have the curriculum orientation before the curriculum in order to arrange the subject according to the student perception system. Teaching and learning activities must be tailored to the students, according to the level of knowledge - ability, age and level of intelligence of students by using a variety of teaching methods. There are ways to encourage teachers to produce more teaching-learning materials. There are ways to encourage teachers to train in accurate measurement and evaluation methods, to have pre-school, during-and-after-school assessments. School-based tutors need to be trained and must be trained in a variety of teaching methods and have at least two in-school tutoring sessions twice a year.